A possible mechanism for the behaviour of high temperature superconductors carrying transport currents in pulsed magnetic fields - Hole, C; Ryan, D; DewHughes, D; Jones, H; Goringe, M; Grovenor, C (1996)
Transport current measurements on low and high temperature superconductors in pulsed magnetic fields up to 41 T have indicated that anomalous voltages appear which cannot be explained as simple inductive artefacts. We propose here a mechanism for their origin and compare the results of numerical simulation with experimental results.